Frontier and developing Asia the next generation of emerging markets - Schipke, Alfred 1959- (International Monetary Fund, 2015)
Frontier economies are receiving increasing attention from policymakers, investors, and academics. Compared with other low-income countries they have experienced rapid growth over the last two decades, giving rise to speculation as to whether they will become the next generation of emerging markets. This book looks at the growing importance of the countries that make up frontier and developing Asia from different angles, including achieving inclusive growth, financial sector deepening, and strengthening policy frameworks.